Contribution to the freshwater gastrotrich fauna of wetland areas of southwestern Ontario (Canada) with redescriptions of seven species and a check-list for North America - Schwank, Peter; Kånneby, Tobias (Zootaxa, 2014)
This study gives additional, detailed information on the freshwater gastrotrich species described and reported from the southwestern regions of Ontario and New Brunswick, Canada by Schwank (1990). Aspidiophorus ontarioniensis, Chaetonotus (Chaetonotus) furculatus, Chaetonotus (Chaetonotus) ontariensis, Chaetonotus (Primochaetus) annae, Ichthydium malleum, Lepidodermella forficulata and Setopus lemnicola are all redescribed. In addition, a complete list of freshwater species currently known from North America is given.